Factors that affect dietary preferences among antenatal mothers at area 25 health centre. - Chiomba, Wisdom Hezekia (Kamuzu University of Health Sciences, 2022)
During the antenatal period dietary preferences change. This affects the growth and maintenance of both the mother and developing foetus. Pregnant women experience the dietary changes in form of aversions and craving. This exploratory qualitative study will be conducted to identify the factors that affect dietary preferences among antenatal mothers. The study setting will be Area 25 Health Centre, and it will involve pregnant women attending antenatal clinic at this health facility. A sample of 15 pregnant women will be conveniently selected as study participants. Data will be collected using interview guide, and content analysis will be used in the analysis of the data collected. The results of this study will help in identifying some of the health-related problems that might have a bearing on dietary preferences in pregnant women, thereby aiding the development of effective strategies of eliminating the identified problems.